Analisis Perbandingan Return dan Resiko (Risk) Saham Syariah dan Non Syariah di LQ45 Bursa Efek Indonesia Periode 2020-2022 - Rahmah; Dahruji, Dahruji (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to determine the difference between the return and risk (risk) of sharia and non-sharia stocks in the LQ45 Indonesia Stock Exchange for the 2020-2022 period. The population in this study is 45 stocks incorporated in LQ45. The stocks listed in LQ45 are already included in the leading most active stocks with a large daily trading volume, so the movement of the LQ45 index greatly affects the movement of the Composite Stock Price Index (IHSG). This research uses a descriptive type of research with a quantitative approach that takes sources from secondary data and data collection techniques with documentation methods. The sample was taken from as many as 23 shares consisting of 16 sharia stocks and seven conventional stocks, using purposive sampling techniques. The data analysis technique used is inferential statistics, which uses different tests to conclude. Based on the normality test that was carried out, the results were obtained that Sharia stock return data is not normally distributed while conventional stock return data is normally distributed, and Sharia stock risk data and conventional stock risk data are both normally distributed. Based on the Mann-Whitney U test, a significant value of > 0.05 was obtained, which is 0.385 for the return rate. In the Independent Sample T-Test test, a significant value was obtained for the risk level of > 0.05, which is 0.523, so it can be concluded that there is no difference in return and risk in Sharia stocks and conventional stocks.